Effect of Microwave Power and Clamping Pressure on the Microwave Welding of Polypropylene Using Silicon Carbide Nanowhiskers as Microwave Susceptor - Foong P.Y.; Voon C.H.; Lim B.Y.; Teh P.L.; Rojan M.A.B.; Parmin N.A.; Gopinath S.C.B.; Arshad M.K.M.; Low F.W.; Mahalingam S.; Manap A.; Rahim R.A.; et al. (Springer Verlag, 2023)
Buckling; Elastic moduli; Joining; Nanowhiskers; Polypropylenes; Reinforcement; Stiffness matrix; Substrates; Tensile strength; Welding; Clamping pressure; Dielectrics property; Joining; Microwave power; Microwave welding; Microwave- irradiations; Nanofiller; Polypropylene nanocomposites; Rapid response; Susceptors; Silicon carbide